DEVELOPMENT OF TECHNOLOGICAL SOLUTIONS OF RECEIVING BLACK AND COLOR ALLOYS WITH APPLICATION OF MID-FREQUENCY INDUCTION FURNACES - D. M. Kukuj; F. I. Rudnitsky; Yu. N. Fasevich; N. N. Sergiyenya; A. S. Sindel (Литьë и металлургия)
The peculiarities of the mid-frequency induction furnace developed by branch of JSC “ATLANT” BSZ together with the company EGES under recommendations of BNTU are considered in the article. Features of technology of melting of experimental alloys in various modes with use disperse and lump the burden materials are analyzed. Necessary conclusions and recommendations on melting conduction are made.